Preface for special section from FLOPS 2014 - CODISH, MICHAEL; SUMII, EIJIRO (Journal of functional programming, 2016)
The 12th International Symposium on Functional and Logic Programming was held in Kanazawa, Japan, June 4–6, 2014. The aim of the Functional and Logic Programming series of conferences is to bring together researchers interested in declarative programming including functional programming and logic programming. The series aims to promote cross-fertilization and integration between the two paradigms and it is traditionally organized and held in Japan.